2019
DOI: 10.13057/biodiv/d200813
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Floristic survey of vascular plant in the submontane forest of Mt. Burangrang Nature Reserve, West Java, Indonesia

Abstract: Abstract. Cahyanto T, Efendi M, Shofara RM. 2019. Short Communication: Floristic survey of vascular plant in the submontane forest of Mt. Burangrang Nature Reserve, West Java, Indonesia. Biodiversitas 20: 2197-2205. A floristic survey was conducted in submontane forest of Block Pulus ​​Mount Burangrang West Java. The objectives of the study were to inventory vascular plant and do quantitative measurements of floristic composition as well as their structure vegetation in the submontane forest of Nature Reserves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
7
1
1
Order By: Relevance
“…Based on the families composition, Lauraceae and Myrtaceae have the highest number of tree species in both sites, followed by Euphorbiaceae and Moraceae. Lauraceae and Myrtaceae families are the richest families in the primary submontane to montane forest of Malesia, as reported by Culmsee et al (2011) in Lore Lindu Sulawesi and Cahyanto et al (2019) in Mt. Tilu, West Java.…”
Section: Species Composition and Succession Statusmentioning
confidence: 76%
See 2 more Smart Citations
“…Based on the families composition, Lauraceae and Myrtaceae have the highest number of tree species in both sites, followed by Euphorbiaceae and Moraceae. Lauraceae and Myrtaceae families are the richest families in the primary submontane to montane forest of Malesia, as reported by Culmsee et al (2011) in Lore Lindu Sulawesi and Cahyanto et al (2019) in Mt. Tilu, West Java.…”
Section: Species Composition and Succession Statusmentioning
confidence: 76%
“…Ketambe. If we compared with the forest vegetation studies in Java Island, Dipterocarpaceae recorded in lowland natural forest, as reported in Bodogol, Gede Pangrango National Park (Helmi et al, 2009) , and were not found in the submontane zone, as reported by Cahyanto et al (2019) in the Mt. Burangrang, Purwaningsih et al (2017) in Mt.…”
Section: Species Composition and Succession Statusmentioning
confidence: 86%
See 1 more Smart Citation
“…Seventy-three species belonging to 38 families were found within the plot, dominated by Araceae and Moraceae families (Table 2 and Table 3). Araceae and Moraceae were the largest families in angiosperms, which have widely distributed from lowland up to montane forest (Backer & van den Brink Jr, 1965, 1968Berg & Corner, 2005), particularly in secondary forest (e.g., Cahyanto et al, 2019;Mutaqien et al, 2008;Widodo & Wibowo, 2012). Compared to other FP in Java and Sumatera, Ir.…”
Section: Results and Discussion The Utilization Block Compared To Protection Block: A Species Compositionmentioning
confidence: 99%
“…The abundance of exotic understory species is an indicator for vegetation succession, as reported by Grant & Loneragan (2001). At the sapling level, the understory woody-form can be used to predict the stand regeneration (Afrianto et al, 2016;Cahyanto et al, 2019;de Carvalho et al, 2017;Irfani, 2016;Rasnovi, 2006;Susanti, 2014).…”
Section: Introductionmentioning
confidence: 99%